A Full Discrete Stabilized Method for the Optimal Control of the Unsteady Navier-Stokes Equations (Journal of Computational Mathematics, 2018)
In this paper, a full discrete local projection stabilized (LPS) method is proposed tosolve the optimal control problems of the unsteady Navier-Stokes equations with equalorder elements. Convective effects and pressure are both stabilized by using the LPSmethod. A priori error estimates uniformly with respect to the Reynolds number areobtained, providing the true solutions are sufficiently smooth. Numerical experiments areimplemented to illustrate and confirm our theoretical analysis.
Keywords: Optimal control; Unsteady Navier-Stokes equations; High Reynolds number; Full discrete; Local projection stabilization.